Adopting sustainability and digital transformation in business in Romania: A multifaceted approach in the context of the just transition - Florina Magdalena Pînzaru; Alina Mihaela Dima; Alexandra Zbuchea; Zoltan Vereș (Amfiteatru Economic Journal, 2022)
This study investigates the many facets of sustainability and digital transformation in business in the context of the fair transition, which will generate multiple challenges and opportunities for companies in various industries. In such a context, a solution to increase resilience and adapt to the fair transition can be identified in the lessons learned by companies due to the application of sustainability and digitization and by understanding the various elements underlying these dimensions. Thus, in order to identify the various elements of this complex framework in practice, based on a semi-structured narrative review of the literature and quantitative analysis, exploring aspects such as the reasons and catalyst factors of the adoption of sustainability and digitalization in companies, the interpenetration of the two concepts in the practice of companies (in production, innovation, customer relationship, logistics, etc.), as well as the associated opportunities and challenges. The research bridges a gap in the academic literature, highlighting the relationships between the digital transformation of business and the adoption of sustainability in companies as a conducive basis for responding to the challenges of the just transition. The analysis details the dimensions of sustainability and digital transition in business in an exploratory model made using structural equations through SmartPLS software applied based on a quantitative study to which 154 professionals, executives, and managers, responded, from local and multinational companies, in different fields of activity. The results obtained after processing 128 valid answers out of the initial 154 are relevant both for the theoretical understanding of the challenges and the practical benefits associated with the digital transformation of business in the context of the development of sustainability strategies. Future lines of investigation are also highlighted.
Keywords: L19; M10; M15; Q01; Q56; 330; sustainability in business; digital transformation; just transition; structural equations; SmartPLS